Unraveling the complexity: Influential factors and trajectories of NGO advancement in China—A fsQCA analysis of 46 Cases - Boyan Zhao; Meiqia Yu (Heliyon)
This study employs fuzzy-set Qualitative Comparative Analysis (fsQCA) to examine 46 Chinese non-governmental organizations (NGOs) and identify the influential factors and developmental trajectories critical for NGO advancement. By integrating the AGIL functional analysis model, the research uncovers that no single factor—be it public expectations, digital technology, governmental support, cross-sector collaboration, key actors, or organizational culture—predominates in fostering advanced development. Instead, it is the combination of these elements that stimulates progress. Five unique pathways for NGO advancement are mapped: internal development, leadership-driven initiatives, strategic external support leveraging, societal adaptation, and an omnibus development approach. Cross-sector collaboration is highlighted as a pivotal factor that enhances NGO networking and facilitates resource sharing and co-creation of value. The study emphasizes the need for proactive public policy engagement, governmental acknowledgment, and fulfillment of public expectations. It underscores the importance of leadership and the cultivation of a robust organizational culture aligned with the entity's mission. This research enriches the theoretical understanding of NGO evolution and provides actionable strategies for NGOs to navigate the complexities of the social sector.